Factors Affecting the Creation of Competitive Advantage of Trade Business Operators in Luang Prabang Municipality, Luang Prabang Province - layaseng, somyot; SIlIVONG, Phonevilay; SIFONGXAY, Sangthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The objectives of this research study were are: to examine the factors affecting the creation of competitive advantage of trade business operators in Luang Prabang Municipality, Luang Prabang Province, and was used a quantitative questionnaire approach. Data were collected from a sample of 170 trade business operators in Luang Prabang Municipality, Luang Prabang Province. The statistics used for analysis include frequency, percentage, mean, standard deviation, and multiple regression analysis using the Enter method. The factors affecting the creation of competitive advantage in trade businesses of entrepreneurs in Luang Prabang Municipality, Luang Prabang Province, overall at a statistical significance level of 0.05, consist of 3 factors: 1) Innovation Factor comprises efforts to seek the application of technology, new ideas and novelties that lead to product development; 2) Cultural and Social Factor comprises societal and customer values in the consumption of goods, and the management and control of trade businesses; 3) Technological Factor comprises the application of technology in trade business operations, the modernity of technology and communication that enables businesses to be aware of changes and adaptation; These factors have a positive relationship with the creation of competitive advantage in trade businesses of entrepreneurs in Luang Prabang Municipality, Luang Prabang Province.